Penerapan Pembelajaran Interaktif Berbasis Wordwall untuk Meningkatkan Hasil Belajar Peserta Didik pada Pembelajaran Pendidikan Pancasila Kelas IV SDN 16 Ampenan - Mutmainnah; Nurhasanah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This classroom action research aims to determine the implementation of Wordwall-Based Interactive Learning to improve student learning outcomes in Pancasila Education for Grade IV students at SDN 16 Ampenan. The study was conducted at SDN 16 Ampenan with the research subjects consisting of all 24 fourth-grade students. The research was carried out in two cycles, each consisting of the following stages: (1) planning, (2) implementation, (3) observation, and (4) reflection. Data were collected through evaluation tests and documentation, and then analyzed descriptively using classical completeness percentages. The results of this classroom action research show that the students’ average score increased from 71.25% in Cycle I to 80.41% in Cycle II. Students who met the minimum mastery criteria (KKM) increased significantly from 62.5% in Cycle I to 83.33% in Cycle II. Based on the findings, it can be concluded that the implementation of Wordwall-Based Interactive Learning effectively improved student learning outcomes in Pancasila Education for Grade IV students at SDN 16 Ampenan, particularly in the topic of understanding the meaning of Pancasila principles and applying them in daily life.